2004
DOI: 10.1159/000077439
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Treatment with Irinotecan and Oxaliplatin Combination in FU-Resistant Metastatic Colorectal Cancer Patients

Abstract: Objectives: As single agents, irinotecan and oxaliplatin are active in colorectal cancer after fluorouracil (FU)-containing regimen failure. Their synergistic activity and non-overlapping toxicity profile are well documented, but more data are needed to explore their exact sequence. The aim of this study was to evaluate the activity and tolerability of irinotecan followed by oxaliplatin in patients with FU-resistant colorectal cancer. Methods: FU resistance was defined as disease progression during or within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…[21][22][23] Some of them are expected to become alternative agents for 5-FU or good partners for 5-FU. [23][24][25][26] In the present study, three of the four candidates, MMC, cisplatin, and docetaxel, showed a positive correlation with the 5-FU spectrum; i.e., a cross-resistance correlation.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Some of them are expected to become alternative agents for 5-FU or good partners for 5-FU. [23][24][25][26] In the present study, three of the four candidates, MMC, cisplatin, and docetaxel, showed a positive correlation with the 5-FU spectrum; i.e., a cross-resistance correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Вельми перспективними для хіміотерапії є препарати групи камптотецинів -зокрема іри-нотекан, і препарат групи платиновмісних сполук -оксаліплатин [11]. Ліпосомальні форми цих препаратів дозволять знизити токсичність і збільшити ефективність терапії.…”
Section: виділення не вирішених раніше частин загальної проблемиunclassified
“…Second-line response rates were not completely satisfactory (FOLFIRI 4% and FOLFOX 15%, respectively), however 19 . The combination of CPT-11 and OHP (IROX regimen) has also been investigated with some success both as second 20,21 and first-line treatment 22 .…”
mentioning
confidence: 99%